2023
DOI: 10.3847/1538-4357/acc316
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation and Molecular Gas Diagnostics with Mid- and Far-infrared Emission

Abstract: With the start of JWST observations, mid-infrared (MIR) emission features from polycyclic aromatic hydrocarbons (PAHs), H2 rotational lines, fine structure lines from ions, and dust continuum will be widely available tracers of gas and star formation rate (SFR) in galaxies at various redshifts. Many of these tracers originate from dust and gas illuminated by UV photons from massive stars, so they generally trace both SFR and gas to varying degrees. We investigate how MIR spectral features from 5–35 μm and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 119 publications
0
5
1
Order By: Relevance
“…The variation in 8 μm emission around these parsec-scale CO peaks reflects the differences in dust heating by local variations in the interstellar radiation field. This is not directly comparable with studies that integrate over much larger (∼ kpc) scales, in which 8 μm is found to trace star formation rate, as well as CO emission, with indications that 8 μm is a stronger CO tracer than a star formation rate tracer (Leroy et al 2023;Whitcomb et al 2023). Because we adopt a CO clump-finding method, we are studying variations in 8 μm brightness among CO-bright regions, rather than studying variations in 8 μm brightness across the ISM unbiased to the presence of molecular gas.…”
Section: Caveats and Future Directionscontrasting
confidence: 83%
See 1 more Smart Citation
“…The variation in 8 μm emission around these parsec-scale CO peaks reflects the differences in dust heating by local variations in the interstellar radiation field. This is not directly comparable with studies that integrate over much larger (∼ kpc) scales, in which 8 μm is found to trace star formation rate, as well as CO emission, with indications that 8 μm is a stronger CO tracer than a star formation rate tracer (Leroy et al 2023;Whitcomb et al 2023). Because we adopt a CO clump-finding method, we are studying variations in 8 μm brightness among CO-bright regions, rather than studying variations in 8 μm brightness across the ISM unbiased to the presence of molecular gas.…”
Section: Caveats and Future Directionscontrasting
confidence: 83%
“…The Spitzer 8 μm band is centered on a prominent PAH feature. Recent work (e.g., Whitcomb et al 2023;Leroy et al 2023) has shown a strong correlation between CO and mid-infrared bands on sub-kpc and galactic scales. Bendo et al (2008) and Cortzen et al (2019) have found the 8 and 6.2 μm PAH bands to trace cold dust rather than warm dust.…”
Section: Ir and Optical Star Formation Indicatorsmentioning
confidence: 99%
“…In the more diffuse regions away from H II regions, the diffuse mid-IR emission should be a good tracer of column density, as the radiation field varies more weakly than the gas column density. This appears to be borne out by a very good local correlation between CO emission, tracing molecular gas column density, and mid-IR emission on ∼100-200 pc scales (see Whitcomb et al 2023a;Leroy et al 2023;Sandstrom et al 2023). In this case, we might expect the lognormal PDFs that we observe to trace the underlying gas column density distribution and to reflect the convolution of turbulence and self-gravity in the diffuse ISM (Burkhart et al 2017).…”
Section: Conversion From Mid-ir Intensity To Gas Column Densitymentioning
confidence: 56%
“…One of the significant challenges in the study of AGN feedback is the difficulty of estimating SFRs (e.g., Kennicutt 1998;Kennicutt et al 2009;Leroy et al 2012;Whitcomb et al 2023). SFR estimation is a complex endeavor with considerable uncertainties, often reaching approximately 0.7 dex (Salim et al 2016).…”
Section: Introductionmentioning
confidence: 99%